Cross-Sectional Distribution of Microplastics in the Rhine River, Germany—A Mass-Based Approach - David Range; Jan Kamp; Georg Dierkes; Thomas Ternes; Thomas Hoffmann (Microplastics)
The focus in microplastic research has shifted from marine ecosystems towards freshwater ecosystems. Still, most studies are based on small sample numbers, both spatially and temporally. Little is known about the spatiotemporal variability of microplastics (MPs) in large river systems such as the Rhine River, Germany. Within our study, we performed four cross-sectional sampling campaigns at two sites in the Rhine River, at Koblenz and Emmerich, involving depth-distributed sampling over a particle size range from 10 µm to 25 mm. For plastic particle analysis, we used both optical and thermoanalytical approaches to determine mass-based polymer concentrations. Our results show that MP variability within the water column is complex, but mostly follows the particles density: the ratio between superficial MPs concentration and mean concentration of the verticals was >1 for lighter polymers with a density below 1.04 g/cm3 and <1 for polymers with a density above 1.04 g/cm3 among all size classes with only a few exceptions, even though the Rouse theory would indicate a more homogeneous distribution for small particle sizes. Large sampling volumes are essential, particularly for larger MP particles, as the coefficient of variation rises with particle size. At our study sites, no significant lateral variation was apparent, while during a flood event, MP concentrations were significantly higher than during low and mean water stages. This study is the first to (i) gain insights into cross-sectional MPs distribution in the Rhine River and (ii) account for particle mass concentrations, and thus lays the foundation for potential future MPs flux monitoring.